2019
DOI: 10.1016/j.wear.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Wear mechanism of spark plasma sintered MWCNTs reinforced zirconia composites under dry sliding conditions

Abstract: In this work multiwall carbon nanotubes (MWCNTs) reinforced 8 mol.% yttria-stabilized zirconia (8YSZ) composites were prepared using attrition milling and spark plasma sintering (SPS, at 1400 °C) in different compositions (0, 1, 5, 10 wt.% MWCNTs). The effect of sliding speed at low (V1= 0.036 m/s) and high (V2= 0.11 m/s) values has been investigated. Outstanding wear improvement at both low/high sliding speed has been reported with the addition of 1 wt.% of MWCNTs. This was most likely attributed to two main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…These data would suggest that the lubrication of the tribosystem only takes place when the concentration of nanotubes is elevated. As a matter of fact, Ahmad et al (2010) reached the highest reduction in friction (80%) by adding ~18 vol% of MWCNTs (~3.9 and ~9.5 vol% were the other selected CNTs contents) when tested at 14 N. In the same way, for Si 3 N 4 /CNTs (Gonzalez-Julian et al, 2014;Hvizdos et al, 2012) and YSZ/CNTs (Kasperski et al, 2013;Lamnini et al, 2019) composites with CNTs amounts in the range of 1.5-15.0 vol%, the lowest friction coefficients (50%-75%) were always recorded at the maximum filler content studied (Table 1).…”
Section: Tribological Response Of Ceramic/cns Compositesmentioning
confidence: 87%
See 1 more Smart Citation
“…These data would suggest that the lubrication of the tribosystem only takes place when the concentration of nanotubes is elevated. As a matter of fact, Ahmad et al (2010) reached the highest reduction in friction (80%) by adding ~18 vol% of MWCNTs (~3.9 and ~9.5 vol% were the other selected CNTs contents) when tested at 14 N. In the same way, for Si 3 N 4 /CNTs (Gonzalez-Julian et al, 2014;Hvizdos et al, 2012) and YSZ/CNTs (Kasperski et al, 2013;Lamnini et al, 2019) composites with CNTs amounts in the range of 1.5-15.0 vol%, the lowest friction coefficients (50%-75%) were always recorded at the maximum filler content studied (Table 1).…”
Section: Tribological Response Of Ceramic/cns Compositesmentioning
confidence: 87%
“…In this way, an enhanced wear resistance is commonly attributed to the improved fracture toughness of CNs composites as compared to monolithic ceramics. CNs fillers arrest or limit the propagation of cracks developed beneath the tribocontact through the occurrence of toughening mechanisms such as crack deflection, bridging or branching (Ahmad et al, 2010;Candelario et al, 2016;Lamnini et al, 2019). The micromechanical response and the contact damage resistance are also important, as the stress fields generated can be redistributed by the fillers located at the grain boundaries (Gonzalez-Julian et al, 2011), restraining the formation of long cracks.…”
Section: Xie Et Al (2014)mentioning
confidence: 99%
“…However, high concentration of CNTs is an obstacle to the formation of lubricating film. The report of Lamnini et al [102] indicated that 10 wt%-MWCNTs difficultly protected tribofilm from the brittle fracture during wear, owing to the structural defects (e.g., agglomeration and porosity) of MWCNTs-reinforced 8 mol% yttriastabilized zirconia (MWCNTs/8YSZ) composites. Adding 1 wt%-MWCNTs into the 8YSZ resulted in a significant improvement in wear resistant, as compared with pure 8YSZ; this mainly attributed to the formation of a continuous tribofilm and the improvements in flexural strength, fracture toughness, and density.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Zirconia is lighter than steel, and its hardness is as par with copper. Zirconia is extremely resistant to heat and corrosion and is often used in high-temperature applications as insulator [30][31][32][33][34]. Because of this characteristic zirconia shows better performance than other materials and has also been used in the manufacture of medical equipment, catalyst helpers, engineering plastics and in nuclear reactors [35][36][37].…”
Section: Introductionmentioning
confidence: 99%